DESAIN STRATEGI PENGEMBANGAN USAHA DENGAN METODE FUZZY-SWOT DALAM ANCAMAN PANDEMI COVID-19 (STUDI KASUS PADA BENGKEL ANUGERAH POKA) - Alfredo Tutuhatunewa; Lidya Pesulima (ALE Proceeding, 2021)
The Covid-19 pandemic has caused the Anugerah Poka workshop to experience a decrease in the number of customers. To maintain its existence, the Anugerah Poka workshop needs to design a strategy, by looking for the suitability of its internal and external strengths. This study aims to design a business development strategy for the Anugerah Poka Workshop using the Fuzzy-SWOT method. The fuzzy-SWOT approach is used to eliminate various structural weaknesses of the SWOT method. The results showed that the strategy that the Anugerah Poka Workshop had to develop was to keep prices low compared to other competitors. The next strategy is the expansion of services in the conditions of the Covid-19 pandemic, in order to continue to increase the existing market share. The following strategy is to improve service while continuing to keep prices low and provide excellent service to customers.